Excel 2010 formulas - Walkenbach, John (Hoboken, NJ Wiley Pub, 2010)
A reference collection of formulas for spreadsheet challenges covers operators, nesting, functions, error values, naming, cell formatting, protection options, array formulas, pivot tables, and auditing
Excel in a nutshell -- Basic facts about formulas -- Working with names -- Introducing worksheet function -- Manipulating text -- Working with dates and times -- Counting and summing techniques -- Using lookup functions -- Tables and worksheet databases -- Miscellaneous calculations -- Borrowing and investing formulas -- Discounting and depreciation formulas -- Financial schedules -- Introducing arrays -- Performing magic with array formulas -- Intentional circular references -- Charting techniques -- Pivot tables -- Conditional formatting and data validation -- Creating megaformulas -- Tools and methods for debugging formulas -- Introducing VBA -- Function procedure basics -- VBA programming concepts -- VBA custom function examples
Includes index
1
Keywords: Microsoft Excel (Computer file); Business -- Computer programs; Electronic spreadsheets